Satreskrim Police Performance in Handling Land Crimes - Suhadi Rizki Herdianto; Evita Isretno Israhadi; Riswadi Riswadi (Interdiciplinary Journal and Hummanity (INJURITY), 2022)
The main task of the State Police of the Republic of Indonesia is to maintain public security and order, to provide protection, protection, and services as well as to enforce the law as regulated in Chapter III Article 13 of Law Number 2 of 2002 concerning the main tasks of the Indonesian National Police. The law is the entire code of conduct that applies in common life, containing alluring rules that can be imposed with a sanction. The law implementation can take place formally and peacefully, but it can also occur because violations of the law must be enforced. Law enforcement by the police also includes criminal acts that occur in land dispute cases found in police jurisdictions throughout Indonesia.